Global Transcription Profiles of Anaplasma phagocytophilum at Key Stages of Infection in Tick and Human Cell Lines and Granulocytes - Nelson, Curtis M.; Herron, Michael J.; Wang, Xin-Ru; Baldridge, Gerald D.; Oliver, Jonathan D.; Munderloh, Ulrike G. (Frontiers in Veterinary Science, 2020)
The incidence of human diseases caused by tick-borne pathogens is increasing but little is known about the molecular interactions between the agents and their vectors and hosts. Anaplasma phagocytophilum (Ap) is an obligate intracellular, tick-borne bacterium that causes granulocytic anaplasmosis in humans, dogs, sheep, and horses. In mammals, neutrophils are the primary target of infection, and in ticks, Ap has been found in gut and salivary gland cells. To identify bacterial genes that enable cell invasion and Ap proliferation in human and tick cells, labeled mRNA from Ap bound to or replicating within human and tick cells lines (HL-60 and ISE6), and replicating in primary human granulocytes, was hybridized to a custom tiling microarray containing probes representing the entire Ap genome. Probe signal values plotted onto a map of the Ap genome revealed antisense transcripts and unannotated genes. Comparisons of transcript levels from each annotated gene between test conditions (e.g., Ap replicating in HL-60 vs. ISE6) identified those that were differentially transcribed, thereby highlighting genes associated with each condition. Bacteria replicating in HL-60 cells upregulated 122 genes compared to those in ISE6, including numerous p44 paralogs, five HGE-14 paralogs, and 32 genes encoding hypothetical proteins, 47% of which were predicted to be secreted or localized to the membrane, while 60% of genes upregulated in ISE6 were hypothetical and 60% of these were predicted to be secreted or membrane associated. In granulocytes, Ap upregulated 120 genes compared to HL-60, 33% of them hypothetical and 43% of those predicted to be secreted or membrane associated. HL-60-grown bacteria binding to HL-60 cells barely responded transcriptionally, while ISE6-grown bacteria binding ISE6 cells upregulated 48 genes. HL-60-grown bacteria did upregulate genes as a function of time, and when placed with ISE6 cells they upregulated genes that were upregulated by ISE6-grown bacteria. Hypothetical genes, which constitute about 29% of Ap genes, played a disproportionate role in most infection scenarios, and particular sets of them were consistently upregulated in bacteria binding/entering both ISE6 and HL-60 cells, suggesting that the encoded proteins play central roles in establishing infection in ticks and humans.